The Role of Stakeholder in Multi-Event and Awarding Model in Indonesia - Nanda Ahmad Firdausy; Nuryadi; Jajat Darajat KN; Agus Gumilar (Universitas Negeri Semarang, 2025)
This study aims to analyze the role of stakeholders in the organization of multi-event sports competitions and evaluate the model of rewarding athletes by the central government in Indonesia. Through a qualitative approach with semi-structured interviews, observation, and documentation, this study involved informants from the Indonesian National Olympic Committee and the Ministry of Youth and Sports. The results show that multi-event management is divided into three main stages, namely preparation, execution, and post-event evaluation, with the NOC playing a central role in the coordination and execution of these activities. On the other hand, the rewarding models applied by the government include medal bonuses, appointment as civil servants, and special access to state agencies. This research recommends the development of a more comprehensive and sustainable reward system, including career transition support and post-retirement mentoring. The findings emphasize the importance of collaboration between stakeholders and policy reforms to support the development of national sports.